Chromosomal microarray analysis in fetuses with central nervous system anomalies: An 8‐year long observational study from a tertiary care university hospital. (30th September 2020) - Santirocco, Maddalena; Plaja, Alberto; Rodó, Carlota; Valenzuela, Irene; Arévalo, Silvia; Castells, Neus; Abuli, Anna; Tizzano, Eduardo; Maiz, Nerea; Carreras, Elena
Abstract: OBJECTIVES: To evaluate the prevalence of DNA copy number variants (CNVs) detected with array comparative genomic hybridization (CGH) in fetuses with central nervous system (CNS) anomalies. Secondary objectives were to describe the prevalence of CNV in specific CNS abnormalities, in isolated defects or associated with other malformations or fetal growth restriction (FGR). METHODS: Observational cohort study in 238 fetuses with CNS anomalies in which an array‐CGH had been performed between January 2009 and December 2017. Pathogenic CNV and variants of unknown significance (VUS) were reported. RESULTS: Pathogenic CNVs were found in 16/238 cases (6.7%), VUS in 18/238 (7.6%), and normal result in 204/238 (85.7%) cases. Pathogenic CNVs were more frequent in posterior fossa anomalies (cerebellar hypoplasia 33%, megacisterna magna 20%), moderate ventriculomegaly (11%) and spina bifida (3.7%). Pathogenic CNVs and VUS were found in 7/182 (3.8%) and 14/182 (7.7%) cases of isolated anomalies, in 9/49 (18.4%) and 4/49 (8.2%) presenting another malformation, and in 0/7 and 0/7 cases with associated FGR ( P = .001, P = .741, respectively). CONCLUSION: These results provide strong evidence toward performing array in fetuses with CNS anomalies, particular in cases of posterior fossa anomalies. The prevalence of pathogenic CNVs is higher in association with other malformations.